Translational Modeling of Psychomotor Function in Normal and AD-Pathological Aging With Special Concerns on the Effects of Social Isolation - Castillo-Mariqueo, Lidia; Giménez-Llort, Lydia (Frontiers in Aging, 2021)
One year after the start of the COVID-19 pandemic, its secondary impacts can be globally observed. Some of them result from physical distancing and severe social contact restrictions by policies still imposed to stop the fast spread of new variants of this infectious disease. People with Alzheimer's disease (AD) and other dementias can also be significantly affected by the reduction of their activity programs, the loss of partners, and social isolation. Searching for the closest translational scenario, the increased mortality rates in male 3xTg-AD mice modeling advanced stages of the disease can provide a scenario of ‘naturalistic isolation’. Our most recent work has shown its impact worsening AD-cognitive and emotional profiles, AD-brain asymmetry, and eliciting hyperactivity and bizarre behaviors. Here, we further investigated the psychomotor function through six different psychomotor analysis in a set of 13-month-old 3xTg-AD mice and their non-transgenic counterparts with normal aging. The subgroup of male 3xTg-AD mice that lost their partners lived alone for the last 2-3 months after ten months of social life. AD’s functional limitations were shown as increased physical frailty phenotype, poor or deficient psychomotor performance, including bizarre behavior, in variables involving information processing and decision-making (exploratory activity and spontaneous gait), that worsened with isolation. Paradoxical muscular strength and better motor performance (endurance and learning) was shown in variables related to physical work and found enhanced by isolation, in agreement with the hyperactivity and the appearance of bizarre behaviors previously reported. Despite the isolation, a delayed appearance of motor deficits related to physical resistance and tolerance to exercise was found in the 3xTg-AD mice, probably because of the interplay of hyperactivity and mortality/survivor bias. The translation of these results to the clinical setting offers a guide to generate flexible and personalized rehabilitation strategies adaptable to the restrictions of the COVID-19 pandemic.